1988
DOI: 10.1128/iai.56.12.3251-3261.1988
|View full text |Cite
|
Sign up to set email alerts
|

Killing of Brucella abortus by bovine serum

Abstract: Studies of the serum bactericidal system in bovine brucellosis were undertaken to investigate the role of the humoral immune response in protection of cattle against the facultative intracellular parasite Brucella abortus. Fresh sera from normal control cattle, infected cattle, and cattle immunized with B. abortus cell envelopes were collected before treatment and during the course of immunization or infection. Normal fresh bovine serum or fresh agammaglobulinemic serum from colostrum-deprived calves was effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Brucellae are sensitive to complement-mediated lysis via the classical pathway (12). Using B. abortus 45/20 and RB51, Corbeil et al concluded that increased sensitivity to the killing activity of complement was attributable to the lack of O antigen (12). Sensitivity to complement was used as a predictor of sensitivity to extracellular killing within the host (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brucellae are sensitive to complement-mediated lysis via the classical pathway (12). Using B. abortus 45/20 and RB51, Corbeil et al concluded that increased sensitivity to the killing activity of complement was attributable to the lack of O antigen (12). Sensitivity to complement was used as a predictor of sensitivity to extracellular killing within the host (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bactericidal assays. Brucella strains were tested for sensitivity to bovine serum by a procedure based on that described by Corbeil et al (12). Sera were collected from the blood of five naive Angus bovine calves and pooled for storage at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…In preliminary experiments, we did not find any effect of 10% FCS on the viability of different strains of B. abortus. The brucellicidal effect of bovine serum is complement dependent (5). Because the FCS used in this study was frozen and thawed at least twice before addition to the minimal essential medium (MEM), its complement activity was probably minimal.…”
Section: Methodsmentioning
confidence: 99%
“…Brucella abortus is a facultative intracellular pathogen that survives ingestion by macrophages and neutrophils (21,30). The ability to survive inside macrophages allows B. abortus to interfere with the function of macrophages and also provides the bacteria with protection from the immune system and the factors in blood which are capable of killing B. abortus (12). After uptake of B. abortus by macrophages, bacteria are found in a membrane-bound vacuole referred to as a phagosome.…”
mentioning
confidence: 99%